Workplace spirituality and job satisfaction. (June 2014) - van der Walt, Freda; de Klerk, Jeremias J.
Abstract In order to obtain an improved understanding of behaviour at work, employees should be studied from physical, psychological, and spiritual dimensions. Although the physical and psychological dimensions of individuals at work have been studied extensively, the spiritual dimension has been neglected for many years. The objective of the current research was to determine the relationship between workplace spirituality and a positive attitude related to work, that is, job satisfaction. A cross-sectional study was conducted with a sample of 600 white-collar workers, chosen from two organizations in different industries in South Africa. The research results indicate that there is a positive relationship between workplace spirituality and job satisfaction. These findings deepen the understanding of personal spirituality, organizational spirituality, and job satisfaction. They bring new insights into the significant role which spirituality plays in the context of the workplace. To survive in the 21st century, organizations need to be spiritually based. This, in turn, will lead to workers being satisfied with their entire work experience.